Die Kämpfe únd schláchten—the struggles and battles of innate-like effector T lymphocytes with microbes - Joyce, Sebastian; Okoye, Gosife Donald; Driver, John P. (Frontiers in Immunology, 2023)
The large majority of lymphocytes belong to the adaptive immune system, which are made up of B2 B cells and the  T cells; these are the effectors in an adaptive immune response. A multitudinous group of lymphoid lineage cells do not fit the conventional lymphocyte paradigm; these are the unconventional lymphocytes. Unconventional lymphocytes—here called innate/innate-like lymphocytes, include those that express rearranged antigen receptor genes and those that do not. Even though the innate/innate-like lymphocytes express rearranged, adaptive antigen-specific receptors, they behave like innate immune cells which allows them to integrate sensory signals from the innate immune system and relay that umwelt to downstream innate and adaptive effector responses. Here we review how NKT cells and MAIT cells—two prototypic innate-like T lymphocytes, which sense their local environment and relay that umwelt to downstream innate & adaptive effector cells to actuate an appropriate host response that confers immunity to infectious agents.